AN EFFECTIVE METHOD FOR DNA EXTRACTION OF MATURE LEAF OF SAPODILLA (Manilkara zapota (L.) van Royen) - Sari, Vega Kartika; Murti, Rudi Hari (AGRIVITA, Journal of Agricultural Science, 2015)
Perennial crop leaves contain polysaccharides, polyphenols, and other secondary metabolites in high concentration. The presence of those compounds inhibit enzymatic activities and amplification of DNA. The existing extraction methods were not able to dissociate the metabolites contaminants of sapodilla (Manilkara zapota (L.) van Royen) leaves and thus resulting in low quality of extracted DNA. The aim of this experiment was to develop an effective method to extract DNA from mature leaf samples of sapodilla (Manilkara zapota (L.) van Royen). Fifth modification of Doyle & Doyle DNA extraction protocol with modified concentration of buffer reagent (consisted of: CTAB 2.8%; NaCl 2.5M; mercaptoethanol 3%, and PVP 2.5%) and repetition of some phase purification (liquid nitrogen; three times CIAA; two times ethanol 70%, RNAse 1µl) generated high quality DNA and clear band of PCR amplification using RAPD primers. Keywords: buffer modifications, DNA extraction, sapodilla